MANAGEMENT OF ARTIFICIAL INTELLIGENCE IN BRAZIL IN THE FACE OF THE CONSTITUTIONAL LEGAL TREATY OF THE DIGITAL ENVIRONMENT (Revista Direito, Políticas Públicas e Desenvolvimento na Amazônia, 2021)
Having as central objective of their research the idea of making computers "think" exactly like humans, creating analysis, reasoning, understanding and obtaining answers for different situations, artificial intelligence has its management in Brazil linked to the legal protection of forms of expression, ways of creating, doing and living, as well as scientific, artistic and mainly technological creations carried out with the help of computers and other electronic components, observing the provisions of the rules of social communication determined by the Federal Constitution. Thus, the management of artificial intelligence in Brazil is necessarily subject to the constitutional legal protection that targets the digital environment established within the scope of our positive law in the face of the duties, rights, obligations and regime inherent in the manifestation of thought, creation, expression and information provided by the human person with the help of computers (article 220 of the Federal Constitution) within the full exercise of the cultural rights granted to Brazilians and foreigners residing in the country (articles 215 and 5 of the Constitution) guided by the fundamental principles of the Federal Constitution 1st to 4th).